Rare Oral Mucous Extravasation Cyst: Case Report - Gaouzi, Rajae El; Chami, Bassima (International Journal of Innovative Research in Medical Science, 2021)
Mucoceles are a benign lesions characterized by an extravasation or retention of mucous in submucosal tissue from minor salivary glands caused most probably by a trauma or habit of lip biting. They usually present as an asymptomatic small superficial swelling, which are knew to occur most commonly on the lower lip, followed by the floor of mouth and in other sites. However, uncommon variants of oral mucoceles sometimes occur. Such lesions may be difficult to diagnose due to their unusual localization and atypical clinical presentation. This paper highlights a rare case of mucocele localized in hard palate in a 63 years old male patient. The lesion was depressed, with a bluish appearance, and it measured 7 mm × 5 mm x 2 mm. Diagnosis is based on clinical characteristics, and confirmed with histological features.